2008
DOI: 10.1002/mnfr.200700158
|View full text |Cite
|
Sign up to set email alerts
|

DGGE and real‐time PCR analysis of lactic acid bacteria in bacterial communities of the phyllosphere of lettuce

Abstract: Food associated indigenous microbial communities exert antagonistic effects on pathogens and may routinely deliver health relevant microorganisms to the GI tract. By using molecular, culture independent methods including PCR-DGGE of 16S rDNA-coding regions and real-time PCR (RT-PCR) as well as BIOLOG metabolic fingerprinting, microbial communities on lettuce were analyzed in samples from fields, from supermarkets and soil. Amplified 16S rRNA gene sequences (57.7%) could be assigned to species previously report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 35 publications
1
34
0
2
Order By: Relevance
“…Mycobacteria (predominantly M. avium) were isolated from 46 samples of salads, leak, lettuce, mushrooms, and other vegetables as well as apple juice and twenty nine isolates were tested (Argueta et al 2000). Zwielehner et al (2008) studied the microbial communities present in the phylosphere of lettuce leaves. After denaturing gradient gel electrophoresis and sequencing analyses, sequences from the genus Mycobacterium were found on leaves as well as soil samples.…”
Section: Mycobacteria In Soilmentioning
confidence: 99%
“…Mycobacteria (predominantly M. avium) were isolated from 46 samples of salads, leak, lettuce, mushrooms, and other vegetables as well as apple juice and twenty nine isolates were tested (Argueta et al 2000). Zwielehner et al (2008) studied the microbial communities present in the phylosphere of lettuce leaves. After denaturing gradient gel electrophoresis and sequencing analyses, sequences from the genus Mycobacterium were found on leaves as well as soil samples.…”
Section: Mycobacteria In Soilmentioning
confidence: 99%
“…Bacterial communities associated with leafy greens have already been described by several culture-independent studies. "First-generation" molecular techniques have been used to describe variation in community structure in the context of leaf surface properties and microbial interactions (5), seasonal variation in the community structure (6), and monitoring of bacterial communities in the food chain (7). The introduction of culture-independent methods, in particular, microbial profiling using high-throughput sequencing to study microorganisms, has revealed more complexity and diversity of the phyllosphere microbiota and has dramatically changed the landscape of microbial ecology (5,(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…Different lifestyle factors and diets were shown to have a significant impact on the faecal microbiota [2,3] .…”
Section: Introductionmentioning
confidence: 99%